The Impact of Public Administration on Cultural Policy and Creative Industries - Salim, Agus; Irwan, Irwan; Iskandar, Khaerul (Journal Social Civilecial, 2024)
This research thus adopts a qualitative design to analyses how public administration influences cultural policy, and its implications for the growth and viability of creative industries. Bureaucracy appears to be central in the formulation, monitoring/assessment, and coordination of cultural policies across the supporting sectors including film, music, and the new media. Employing a qualitative research approach involving interviews with policy makers, public administrators, representatives from cultural industries, analyses of available policy documents and an ethnographic approach to cultural events, the study identified important policy issues regarding policy formulation, funding sources and policies and cultural regulation. These papers suggest that sound cultural policies unlock potential for innovation and sustainability in creative economy sectors, in terms of appropriate facilities, funds, and legal framework. Nevertheless, obstacles such as limited access to resources, inadequate performance of the administrative system, and dispersed control over the process compromise the execution of these strategies. The research enriches the knowledge base by identifying the potentially missing or underexplored aspects of PA’s impact on the creative industries’ growth and proposing strategies for improvement. In conclusion, the present study enforces a necessity to develop a balanced and easily comprehensible vision of the function and potential approaches on the part of the public administration to maintain the long-term stability and further development of the creative industries as a significant factor for economic growth and cultural diversification.